Human cytolytic and interferon gamma-secreting CD8+ T lymphocytes specific for Mycobacterium tuberculosis - Lalvani, A; Brookes, R; Wilkinson, R J; Malin, A S; Pathan, A A; Andersen, P; Dockrell, H; Pasvol, G; Hill, A V (Proceedings of the National Academy of Sciences - PNAS, 1998)
Protective immunity to Mycobacterium tuberculosis is poorly understood, but mounting evidence, at least in animal models, implicates major histocompatibility complex class I-restricted CD8+ T cells as an essential component. By using a highly sensitive assay for single cell interferon gamma release, we screened an array of M. tuberculosis antigen-derived peptides congruent with HLA class I allele-specific motifs. We identified CD8+ T cells specific for epitopes in the early secretory antigenic target 6 during active tuberculosis, after clinical recovery and in healthy contacts. Unrestimulated cells exhibited peptide-specific interferon gamma secretion, whereas lines or clones recognized endogenously processed antigen and showed cytolytic activity. These results provide direct evidence for the involvement of CD8+ cytotoxic T lymphocytes in host defense against M. tuberculosis in humans and support current attempts to generate protective cytotoxic T lymphocyte responses against M. tuberculosis by vaccination.